Taking it personal? Investigating regime personalization as an autocratic survival strategy. Issue 5 (3rd July 2020) - Grundholm, Alexander Taaning
ABSTRACT: Personalist autocracy is on the rise globally. Dictators' increasing tendency to concentrate power in their own hands has major implications for the political stability of autocracies. However, the exact nature of this impact is unclear. On the one hand, regime personalization has been linked to a reduction in the likelihood of coups. On the other hand, personalization has also been linked to an increase in the likelihood of civil war. This article reconciles these findings and argues that personalization involves a trade-off between different kinds of threats against a dictator. By increasing the degree of personalization, dictators reduce their vulnerability to insider challenges while at the same time increasing their vulnerability to outsider challenges. These expectations are corroborated by a time-series cross-sectional analysis of a global sample of autocratic regimes. The findings help shed light on recent instances of longstanding autocrats being overthrown during episodes of mass mobilization.